ANALISIS SISTEM PENDUKUNG KEPUTUSAN UNTUK PEMBERIAN KEPUTUSAN PEMBEBASAN BIAYA BAGI SISWA YANG KURANG MAMPU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (STUDY KASUS MI HIDAYATUUL MUBTADIIN SRIKATON ADILUWIH) - Dedi Irawan; Nurlaeili Mafrudhoh (Jurnal TAM (Technology Acceptance Model), 2016)
Decision support systems are generally defined as a system capable of producing solutions or handling problems. Decision support system is not intended to replace the role of decision-makers, but to help and support the decision makers. In the role of decision support systems in the overall context of information systems aimed at improving performance through the application of information technology and determine the approach used in the decision making process, to evaluate the interactive election. One method that is often used in decision support systems is Simple Additive weighting method (SAW). Simple Additive weighting method (SAW) have been selected because it can determine the weight values for each attribute, followed by the ranking process that will select the best alternative from a number of alternatives. In this case the alternative in question is the determination of the best teachers in MI Hidayatuul Mubtadiin Srikaton Adiluwih using SAW method (simple additive weighting). With ranking method is expected to be more precise assessment because it is based on the value of the criteria and weighting that have been specified so that it will get maximum results. Decision support system is designed using the programming language Borland Delphi 7.